Ticks and Lyme borreliosis in an alpine area in northeast Italy. - Nazzi, F; Martinelli, E; Del Fabbro, S; Bernardinelli, I; Milani, N; Iob, A; Pischiutti, P; Campello, C; D'Agaro, P (Med Vet Entomol, 2010)
A 2-year study was conducted in a mountainous area of northeast Italy to evaluate the occurrence and distribution of ticks, as well as to assess the prevalence of the spirochaete Borrelia burgdorferi sensu lato. All ticks collected were Ixodes ricinus L. (Parasitiformes: Ixodidae). In general, most nymphs and adult ticks were collected from April to July. Tick density was highly variable among sites; however, two areas with different infestation levels were recognized. Prevalences of B. burgdorferi s.l. in nymphal stages were rather variable between sites; overall the prevalence of infected nymphs in the whole area was slightly higher than 20%. The prevalence of B. burgdorferi s.l. in nymphs does not seem to be correlated with nymph density. The correlation between the incidence of Lyme borreliosis (reported human cases/1000 inhabitants/year) and Borrelia prevalence in nymphs was not significant, although a significant correlation was found between borreliosis incidence and nymph density.
Keywords: Animals; Borrelia burgdorferi; Climate; Ecology; Humans; Incidence; Italy; Ixodes; Lyme Disease; Nymph; Population Density; Prevalence; Seasons; Ticks